Determination of the Location of Kedungkandang Irrigation in Malang City Based on Soil Quality, Climate, and Availability of Water Sources - Sholikhah, Rachmawati; Irma Triani, Syahdina (PANGRIPTA, 2024)
This study aims to determine the location of Kedungkandang irrigation in Malang City by considering three main factors, namely soil quality, climate conditions, and availability of water sources. Kedungkandang irrigation, which has been operating since the Dutch colonial era, has an important role in supplying water to agricultural land in South Malang until now. This study uses direct observation methods, archival documentation, and interviews with experts to identify these factors. The results of the study indicate that good physical soil quality, supportive climate conditions, and stable water availability are the keys to the success of irrigation operations for more than a century. In addition, factors such as the type of crops irrigated and the direction of city development also have an impact on the sustainability of irrigation. This study provides important insights into the importance of proper planning in selecting irrigation locations to ensure the sustainability of infrastructure in the future.